Estrogen receptors and estetrol-dependent neuroprotective actions: a pilot study. Issue 1 (January 2017) - Tskitishvili, Ekaterine; Pequeux, Christel; Munaut, Carine; Viellevoye, Renaud; Nisolle, Michelle; Noël, Agnes; Foidart, Jean-Michel
Abstract : Estetrol (E4) has strong antioxidative, neurogenic and angiogenic effects in neural system resulting in the attenuation of neonatal hypoxic–ischemic encephalopathy. We aimed to define the role of estrogen receptors in E4-dependent actions in neuronal cell cultures and prove the promyelinating effect of E4. In vitro the antioxidative and cell survival/proliferating effects of E4 on H2 O2 -induced oxidative stress in primary hippocampal cell cultures were studied using different combinations of specific inhibitors for ERα (MPP dihydrochloride), ERβ (PHTTP), GPR30 (G15) and palmytoilation (2-BR). LDH activity and cell survival assays were performed. In vivo the promyelinating role of different concentrations of E4 (1 mg/kg/day, 5 mg/kg/day, 10 mg/kg/day, 50 mg/kg/day) was investigated using the hypoxic–ischemic brain damage model in the 7-day-old immature rats before/after the induction of hypoxic–ischemic insult. Myelin basic protein (MBP) immunostaining was performed on brain coronal sections. Our results show that LDH activity is significantly upregulated in cell cultures where the E4's effect was completely blocked by concomitant treatment either with ERα and ERβ inhibitors (MPP and PHTPP, respectively), or ERα and ERβ inhibitors combined with 2-BR. Cell survival is significantly downregulated in cell cultures where the effect of E4 was blocked by ERβ inhibitor (PHTTP) alone. The blockage of GRP30 receptor did affect neither LDH activity nor cell survival. MBP immunostaining is significantly upregulated in E4-pretreated groups at a concentration of 5 mg/kg/day and 50 mg/kg/day E4, whereas the MBP-positive area OD ratio is significantly increased in all the E4-treated groups. E4's antioxidative actions mostly depend on ERα and ERβ, whereas neurogenesis and possibly promyelinating activities might be realized through ERβ.